Treatment of Extensively Comminuted Mandibular Fracture with the Aid of a Condylar Positioning Device - Abd Jabar Nazimi; Tengku Ezulia; Jothi Raamahlingam Rajaran; Siti Salmiah Mohd Yunus; Syed Nabil (Case Reports in Dentistry)
We describe a case of extensively comminuted mandibular fracture that extends bilaterally to the angle of mandible successfully treated with the use of condylar positioning device (CPD). This simple, yet effective, technique that almost exclusively described in orthognathic surgery is useful when advance surgical techniques such as pre- or intraoperative landmark identification may not be readily available. CPD technique optimizes the manual manipulations of the comminuted distal segments during fracture reduction and internal fixation. At the same time, it allows greater control of the proximal segments to avoid further surgical complication.